Participatory varietal selection in rapeseed-mustard - Asif M Iqbal,; S Najeeb,; Asif B. Shikari,; Gulzaffar,; Sabeena Naseer,; Shaheena Nagoo,; Aziz Mutaba,; ZA Dar,; G Ali,; I Abidi,; MA Ganai,; GA Parray, (Journal of Oilseed Brassica, 2026)
The present investigation of PVS in rapeseed-mustard comprised of nine mother trials were successfullyconducted across four predominant oilseed districts of Kashmir valley during 2013-14 and 2014-15. Inaddition to it, twenty four baby trials (12 each year) of Shalimar sarson-1 and Shalimar sarson-2 each of500m2 area along with farmer’s variety as check were conducted across the villages and over the years. Allthe trials were managed by the farmers under the supervision of breeder. The farmer walk was organized bythe researchers at the farmer’s field prior to harvest of the crop and farmers were allowed to select thevarieties in a secret ballot box. On the basis of overall ranking of varieties by the farmers, the Shalimarsarson-1 & Shalimar sarson-2 (not notified) were the selected by the farmers across most of the districts.The main aim of the study was to increase the adoption of modern varieties to suit their agroecologicalnichesof the valley.